Adaptasi Desain Pasar Tradisional di Era New Normal Dalam Mendukung Wisata Belanja - Sri Lilianti Komariah; Fuji Amalia; Ria Dwi Putri (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2021)
During approximately one year of the COVID-19 pandemic, the obligation to carry out the 3M health protocol formed many new habits. This new habit brings everyone to the new normal era, where things that were previously rarely done become mandatory to be implemented. Both modern and traditional markets are obliged to facilitate visitors to still be able to obey health protocols. However, compared to modern markets, traditional market managers tend to be less able to provide facilities that can support the implementation of health protocols, especially in terms of building design. This study aims to find solutions for adapting traditional market designs in the new normal era. It is hoped that this research can be useful as a design reference for planning or developing traditional markets in the face of the new normal era. The research method used is a qualitative analysis method with research results in the form of adapting traditional market building designs in the new normal era by referring to six design characteristics that are adapted to health protocols, namely having lots of air ventilation, circular market stall layout, one-way circulation system, and expanding the entrance area as a starting point for screening. Futhermore responding to pandemic conditions, efforts to support social interaction as one of the attractions for shopping at traditional markets can be done by placing acrylic barriers, open spaces, and areas for drive thru.